2017
DOI: 10.1007/s10067-017-3754-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation in chronic widespread pain: a systematic review and meta-analysis

Abstract: Chronic non-specific widespread pain (CWP) including fibromyalgia (FMS) is characterized by widespread pain, reduced pain threshold, and multiple tender points on examination, causing disability and decreased quality of life. Vitamin D has been proposed as an associated factor in CWP. This meta-analysis aimed to explore the benefit of vitamin D supplementation in the management of CWP. A comprehensive search of the CENTRAL, MEDLINE, and Embase databases was performed from inception through January 2017. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 25 publications
4
39
0
9
Order By: Relevance
“…In this regard, it is demonstrated that following the trial, mean interictal level of CGRP in patients who received 2000 IU/ d of vitamin D was significantly lower than that of placebo receiving group. These results tie well with most of the previous studies wherein vitamin D supplementation effects were investigated in relation to pain, headache or migraine [8,[29][30][31][32][33].…”
Section: Discussionsupporting
confidence: 90%
“…In this regard, it is demonstrated that following the trial, mean interictal level of CGRP in patients who received 2000 IU/ d of vitamin D was significantly lower than that of placebo receiving group. These results tie well with most of the previous studies wherein vitamin D supplementation effects were investigated in relation to pain, headache or migraine [8,[29][30][31][32][33].…”
Section: Discussionsupporting
confidence: 90%
“…A major Cochrane Database systematic review has also precluded a large beneficial effect of vitamin D supplementation in the treatment of painful conditions (30) . Some recent reviews showed no clear benefit of vitamin D supplementation in treatment of chronic non-specific musculoskeletal pain (50) , while other reviews showed that vitamin D supplementation is effective in reducing the pain score in chronic widespread pain (31,51,52) . Currently, vitamin D supplementation cannot be considered as an independent treatment for chronic pain (53) .…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of randomised controlled trials that aimed to investigate the impact of vitamin D supplement on non-specific LBP or LBP resulting from osteoporosis showed that vitamin D supplementation is no more effective than placebo (27) and a major Cochrane Database systematic review has precluded a large beneficial effect of vitamin D in the treatment of painful conditions (30) . Despite these findings, a recent review showed that vitamin D supplementation is effective in reducing the pain score in chronic widespread pain (31) .…”
mentioning
confidence: 99%
“…They all conclude that there is modest level of evidence that vitamin D supplementation is efficient to treat chronic pain. In line, reviews of published randomized controlled trials report that vitamin D induces a significantly greater mean decrease in pain score for patients with chronic pain, compared with placebo [14][15][16], especially when patients display calcidiol [25(OH)D] levels below 30 nmol/L [17].…”
Section: Introductionmentioning
confidence: 94%